Testicular schistosomiasis presented as complicated epididymo-orchitis in a teenager - Faisal Ahmed; Mohamed Badheeb; Ebrahim Al-Shami; Saleh Al-wageeh; Qasem Alyhari; Fayed Al-Yousofy; Saif Ghabisha (Elsevier, 2022)
Schistosomiasis is a trematodes infection that causes significant morbidity and mortality in the Middle East, particularly in Yemen. Despite its impact, testicular schistosomiasis is still viewed as an uncommon illness. We present a 15-year-old child with left testicular pain and fever for three days diagnosed as left epididymo-orchitis based on the clinical and ultrasonographical findings. The patient was treated empirically with intravenous antibiotics alongside supportive care without improvement after one week. Ultrasonography follow-up showed that the left testis was heterogeneously enlarged without intratesticular blood flow, suggesting left testicular torsion. Immediate scrotal exploration was performed, revealing a dark, congested, and 180° twisted left testicle. Thus, an orchiectomy was performed. The specimen's histology revealed calcified ova of Schistosoma haematobium. In conclusion, even though testicular schistosomiasis is rare, clinicians should provide a thorough clinical evaluation and histopathological analysis for resected specimen, particularly in high-risk patients.